The Relationship of Home Environmental Conditions with the Status of Acute Respiratory Infections in Adults in the East City Health Center Area - Alysa Salsabillah Ahmad; Nasrun Pakaya; Sartika (Universitas Muhammadiyah Palu, 2026)
Acute Respiratory Infection (ARI) is one of the health problems that still often occurs in the community and can be affected by unhealthy home environmental conditions. Home environmental conditions such as poor ventilation, lack of lighting, high humidity, occupancy density, and inadequate sanitation can increase the risk of ISPA. This study aims to determine the relationship between home environmental conditions and ISPA status in adults in the East City Health Center area. This study uses a quantitative design with a cross sectional approach. The study population amounted to 1,720 adults who had experienced ISPA in the East City Health Center area. A sample of 95 respondents was obtained using the purposive sampling technique based on the Slovin formula. The research instrument used questionnaires of home environmental conditions and medical record data to determine ISPA status. Data analysis was carried out univariate and bivariate using the Spearman Rho test with a significance level of ? = 0.05. The results of the study showed that most of the respondents had poor home environmental conditions and experienced severe ARI. The results of the statistical test showed that there was a significant relationship between the condition of the home environment and the status of ISPA in adults in the East City Health Center area with a p-value of < 0.05. This study concludes that poor home environmental conditions increase the risk of severe ISPA in adults.